PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI DINAS KETENAGAKERJAAN KOTA MEDAN - Dewi Kartika Saragih, Natasya; Oktavia, Sulastria Cici; br. Sembiring, Veramika; Sinaga, Dearma (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2023)
Dinas Ketenagakerjaan as one of work units of the medan city regional apparatus that carries out government authority inThe field of employment in the Kota medan. Dinas Ketenagakerjaan is an agency that is developing which is inseparable from problems of career developmend and work motivation for employees which causes a decrease in imployee performance. Career development and work motivation are factors that can increase and decrease employee performance, this study aims to determine whether the influence of career development and work motivation affects employee performance in Dinas Ketenagakerjaan Kota Medan. The author also limits this research so that it is limited to a employee who are already civil servants. The population of this study is 58 respondents, the data anlysis method used is multiple linear regression, parsial test (t), simultaneous test (F) and test of the cpfficient of determination (R2) From research it is known that career development with a significant value of 0,041 < 0,05 it a value result thitug 2.089 > ttabel 1,673, it can be concluded partially that career devloment has a positive and significant effect on employee performance. Work motivation with significant value 0,041 < 0,05 it a value result thitug 4,299 > ttabel 1,673 it can be concluded partially that work motivation has a positive and significant effect on employee performance. When seen from the results of the F test where the value is significant 0,000<0,05 with value results Fhitung (19,333) < Ftabel (3,165) it can be concluded that career development and work motivation together have a positive and significant effect on employee performance The test results of the coefficient of determination in this study obtained a value R2 as big 0,413. This shows that employee performance is influenced by career development and work mitivation 54,9 % whilw the rest 45,1% influenced by other factors not included in this study.